1997
DOI: 10.1021/ma961039k
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Aggregates with Crystalline Cores:  The System Polyethylene−Poly(ethylenepropylene)

Abstract: We have studied the aggregation behavior of polyethylene−poly(ethylenepropylene) (PE−PEP) diblock copolymers dissolved in decane. For this purpose PE−PEP diblock copolymers of various molecular weights, compositions, and degrees of deuteration were synthesized via an anionic route. The structure and morphology of the aggregates was studied by small angle neutron scattering varying both the contrast as well as the polymer labeling. We found a hierarchy of structures:  The PE component crystallizes in lamellar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
212
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(223 citation statements)
references
References 33 publications
9
212
1
Order By: Relevance
“…) exp(-u 2 )∫ 0 u exp(t 2 ) dt, which results from the averaging for an isotropic ensemble of platelets 7 and exhibits the following asymptotic behavior: for u f ∞, 2D(u)/u f 1/u 2 and for u f 0, D(u)/u f 1. The scattering of the molecules in solution was added (eq 5 with an exponent P ) 5 / 3 ) giving an additional contribution to the intensity at high Q.…”
Section: D(u) Defines the Dawson Function D(u)mentioning
confidence: 99%
See 2 more Smart Citations
“…) exp(-u 2 )∫ 0 u exp(t 2 ) dt, which results from the averaging for an isotropic ensemble of platelets 7 and exhibits the following asymptotic behavior: for u f ∞, 2D(u)/u f 1/u 2 and for u f 0, D(u)/u f 1. The scattering of the molecules in solution was added (eq 5 with an exponent P ) 5 / 3 ) giving an additional contribution to the intensity at high Q.…”
Section: D(u) Defines the Dawson Function D(u)mentioning
confidence: 99%
“…The geometrical and density parameters have been evaluated from the fit of the data for both contrast conditions in terms of an ensemble of finite extended disks forming a correlated arrangement (eqs [6][7][8]. The results are reported in Table 3 and reveal almost the same lateral extension of the disks as in the case of sample 4 while the amounts of polymer and wax contained by the layers is significantly higher.…”
Section: D(u) Defines the Dawson Function D(u)mentioning
confidence: 99%
See 1 more Smart Citation
“…Small-angle neutron scattering (SANS) technique exploiting on one side the strength of contrast matching and, on other side, the wide length scale explored, from 1nm up to 1m, is a dedicated technique to investigate and elucidate complex morphologies such as those occurring in a wax-polymer-oil system (Richter et al, 1997;Leube et al, 2000;Monkenbusch et al, 2000;Schwahn et al, 2002aSchwahn et al, , 2002bAshbaugh et al, 2002;Radulescu et al, 2003Radulescu et al, , 2004Radulescu et al, , 2006Radulescu et al, , 2008Radulescu et al, , 2011. An eloquent example is that of diblock polymers (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The overall shape thus depends on the interplay between the interfacial energy of the crystalline block and the solvent, and the stretching within the amorphous block [4]. Thus, the micellar architecture is strongly influenced by the crystallization conditions, such as temperature [9], and composition of the block copolymers [3, 5-By changing composition, solvent, and structure of the crystalline block, spherical [7,[11][12][13], cylindrical [10,14,28], and lamellar micelles have been obtained [1,3,5,15,29]. Recently, Winnik et al reported the possibility to obtain cylindrical micelles with controlled dimensions and architectures of organometallic block copolymers containing the crystallizable polyferrocenyldimethylsilane as one block.…”
Section: Introductionmentioning
confidence: 99%